2010
DOI: 10.1007/s00424-010-0886-1
|View full text |Cite
|
Sign up to set email alerts
|

In airways ATP refills sarcoplasmic reticulum via P2X smooth muscle receptors and induces contraction through P2Y epithelial receptors

Abstract: In airway smooth muscle (ASM), ATP induces a contraction associated with the increase of [Ca(2+)](i). Cytosolic Ca(2+) is extruded to the extracellular space by the Na(+)/Ca(2+) exchanger (NCX) in its normal mode. Some agonists activate the reverse mode of the NCX (NCX(REV)), inducing Ca(2+) entry. We investigated whether ATP, via P2X receptors, activates the NCX(REV) and whether the increment in [Ca(2+)](i) is used for contraction or for the sarcoplasmic reticulum (SR) refilling in guinea pig ASM. ATP contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
(46 reference statements)
2
28
0
Order By: Relevance
“…First, the relaxation was mimicked by P2Y receptor agonists (UTP and ATPγS) and was inhibited by NEM, which is known to uncouple G proteins from several membrane receptors. NEM findings are in agreement with our previous results [9], which indicated that P2Y receptors are coupled to G q/11 in airway smooth muscle. Therefore, when stimulated, P2Y receptors promote IP 3 , initiating the signal pathway for [Ca 2+ ]i increase, and this induces relaxation [9].…”
Section: % Of Relaxation (Histamine Contraction)supporting
confidence: 94%
See 4 more Smart Citations
“…First, the relaxation was mimicked by P2Y receptor agonists (UTP and ATPγS) and was inhibited by NEM, which is known to uncouple G proteins from several membrane receptors. NEM findings are in agreement with our previous results [9], which indicated that P2Y receptors are coupled to G q/11 in airway smooth muscle. Therefore, when stimulated, P2Y receptors promote IP 3 , initiating the signal pathway for [Ca 2+ ]i increase, and this induces relaxation [9].…”
Section: % Of Relaxation (Histamine Contraction)supporting
confidence: 94%
“…NEM findings are in agreement with our previous results [9], which indicated that P2Y receptors are coupled to G q/11 in airway smooth muscle. Therefore, when stimulated, P2Y receptors promote IP 3 , initiating the signal pathway for [Ca 2+ ]i increase, and this induces relaxation [9]. Second, this relaxation was only inhibited by co-application of suramin and RB2, the former is known to antagonize all P2Y receptors but not P2Y 4 and the latter inhibits all P2Y receptors but has no activity on P2Y 2 [7,30,31,33].…”
Section: % Of Relaxation (Histamine Contraction)supporting
confidence: 94%
See 3 more Smart Citations